2000
DOI: 10.1507/endocrj.47.103
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Bone Mineral Density and Serum Bone-Related Proteins in Premenopausal and Postmenopausal Japanese Women.

Abstract: Abstract.The purpose of this cross-sectional study was to characterize the age-related change in bone metabolism during the pre-and postmenopausal periods, and to define the standard levels of three serum markers of bone metabolism, pyridinoline cross-linked carboxyterminal telopeptide of type I collagen (ICTP), carboxyterminal propeptide of type I procollagen (PICP), and bone gla protein (BGP), in Japanese adult women. The bone mineral density (BMD) of the lumbar spine (L2-L4) and the serum levels of ICTP, PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The results of the present study indicated that the levels of OC (P<0.01), PICP (P<0.05) and ICTP (P<0.01) were all increased in the OVX group. This may be due to the lack of estrogen resulting in hyperactivity in osteoclastic bone resorption and leading to a subsequent increase in bone resorption markers (39). Regardless of whether sCT and ASA were used alone or in combination, they were able to inhibit the high bone turnover observed in OVX rats; however, there was no significant difference between the effectiveness of the treatments, alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicated that the levels of OC (P<0.01), PICP (P<0.05) and ICTP (P<0.01) were all increased in the OVX group. This may be due to the lack of estrogen resulting in hyperactivity in osteoclastic bone resorption and leading to a subsequent increase in bone resorption markers (39). Regardless of whether sCT and ASA were used alone or in combination, they were able to inhibit the high bone turnover observed in OVX rats; however, there was no significant difference between the effectiveness of the treatments, alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, renal function was not considered to have affected the changes in any of the serum markers focused on in our study. ICTP differed between premenopausal and postmenopausal women, and the number of years after menopause was also associated with increasing ICTP . Age was associated with increasing serum TRACP‐5b activity in healthy women and increasing serum BAP in healthy men and women .…”
Section: Discussionmentioning
confidence: 91%
“…ICTP differed between premenopausal and postmenopausal women, and the number of years after menopause was also associated with increasing ICTP. 24 Age was associated with increasing serum TRACP-5b activity in healthy women 8 and increasing serum BAP in healthy men and women. 25 In our study, half of patients were male, while most of the women were likely postmenopausal, and so the effect of menopausal status on our results was considered limited.…”
Section: Discussionmentioning
confidence: 95%